Home Environmental Monitoring System and Medicine Reminder for Elderly Assistance - Azami, Mohammad Alifhakim; Mohd Muji, Siti Zarina (Evolution in Electrical and Electronic Engineering, 2025)
The Home Environmental Monitoring System and Medicine Reminder for Elderly Assistance project aims to provide caregivers with an accessible and efficient system for remotely monitoring the home environment and medication schedules of their elderly parents. The system utilizes sensors, including BME280, MLX90614, AHT21, MQ-2, MQ-7, MQ-135, and RTC DS3231, integrated with an ESP32 microcontroller, to continuously track key environmental parameters such as temperature, humidity, and air quality while managing timely medication reminders. Google Sheets serves as a bridge for seamless communication between the hardware and a customized Kodular-developed application, enabling caregivers to receive immediate reminders and notifications on their mobile phones to address missed medication timings. Powered by a simple 5V supply, the device is easily installable and maintainable in a home setting. This integrated system enhances the health and well-being of older individuals while offering caregivers peace of mind and improved management of their relatives’ health, thereby increasing daily care levels. Evaluation reveals a 98.3% success rate for the medicine reminder system and stable hardware performance with 99.5% sensor accuracy over 24-hour operation.